Do Silicon-Based Radicals Play a Role in Quartz-Induced Hemolysis and Fibrogenicity? - N. S. Dalal; X. Shi; V. Vallyathan (The National Institute for Occupational Safety and Health (NIOSH), 1988)
"Correlated spectroscopic and cytotoxicity measurements were made on newly crushed silica to find whether the fracture-induced, silicon related (Si-0· or Si· type) free radicals play a direct role in the mechanism of hemolysis by silica particles. The free radical content of the silica particles was controlled through the radical decay, thermal annealing, and boiling processes, and was followed with electron spin resonance spectroscopy. Portions of the same sample were evaluated for their hemolytic potential, employing sheep erthyrocyte and optical absorption techniques. The results indicate little, if any, correlation between the amount of the silicon-based radicals and the hemolytic potential of the fresh dusts, but these or related radical sites might be contributors to silica cytoxicity and fibrogenicity via peroxidative pathways .INTRODUCTIONIn an earlier convnunication (1.) from our laboratory it was reported that mechanical crushing of coal and quartz under normal air atmosphere generates free rad;cals on the particle surfaces, and that these radicals decay with time, hence pointing to a higher toxicity of fresh dusts in relationship to pneumoconiosis and silicosis. More recently Fubin; et al.(2) have also reported the detection by electron spin resonance (ESR) of the formation of SiO· and Si·-type of radicals from quartz particles crushed under atmospheric conditions. In agreement with earlier ESR studies on single crystals of quartz crushed under high vacuum (10-10 torr) (3) and subsequent exposure to air (3), and to other gases (4), these radicals were identified (2) as being formed by the hemolytic cleavage of the Si-0-Si bonds and the reactions of the Si· and SiO· ,radical with atmosphere. Fubin; et al. (2) also suggested that these radicals might be involved in the mechanism of the fibrotic action by silica, either by transforming the particle surface into a selective oxidating agent or as an initiator of a sequence of reactions leading to fibrosis. Earlier Gabor and Anea (5) had reported that lipid peroxidation caused by free radicals on the silica surface might be involved in the red blood cell membrane damage. Thus far, however, no parallel cytotoxicity, fibrogenicity, and free radical studies on a given Quartz dust sample have been reported, except for some earlier work from our laboratory (1,6,7). We now present more recent results obtained from parallel cytotoxicity, fibrogenicity, and free radical measurements on a freshly made quartz dust. The dust’s free radical content was measured using ESR spectroscopy while its cytotoxicity poteni1al was estimated via hemolysis. Hemolysis was employed as the tox1c1ty test because it 1s a widely used method for estimating the potential of a dust for disrupting the cell membrane (8). The f1brotic potential was followed.by measuring the dust-induced lipid perox1dat1on. us1ng linole1c ac1d as a model lipid. As discussed below, the results obtained suggest new clues.to the mechanism of the Quartz-related cytotoxicity and fibrogenicity."